Human resource management - Stone, Raymond J (Milton, Qld. : John Wiley & Sons Australia, 2008)
Celebrating its twentieth year in publication, Ray Stone's Human resource management is the longest running and most successful Australian textbook ever produced in the field of HRM. In this sixth edition, the content has been thoroughly revised to reflect contemporary issues and practices in HRM, including the impact of the Workplace Relations Amendment (Work Choices) Act 2005. Topical issues such as worklife balance, the ageing population and the skills shortage are thoroughly explored in terms of their effect on organisations, employees and the HR manager.
Part 1. Introducing HRM -- Strategic human resource management -- Human resource planning -- Human resource information management systems -- Human resource management and the law -- Part 2. Determining, attracting and selecting human resources -- Job analysis, job design and quality of work life -- Recruiting human resources -- Employment selection -- Part 3. Developing human resources -- Appraising and managing performance -- Human resource development -- Career planning and development -- Part 4. Rewarding human resources -- Employee remuneration -- Incentive remuneration -- Employee benefits -- Part 5. Managing human resources -- Industrial relations -- Managing workplace relations -- Managing change -- Negotiating in the workplace -- Employee health and safety -- Managing diversity -- Part 6. Human resources in a changing world -- International human resource management -- Managing international assignments -- Part 7. Evaluating human resource management -- Assessing human resource management effectiveness.
Keywords: Personnel management -- Australia; Personnel management